Fertility outcomes following obstetric fistula repair: a prospective cohort study - Dawn M. Kopp; Jeffrey Wilkinson; Angela Bengtson; Ennet Chipungu; Rachel J. Pope; Margaret Moyo; Jennifer H. Tang (BMC, 2017)
Abstract Background Obstetric fistula (OF) is a maternal morbidity associated with high rates of stillbirth, amenorrhea, and sexual dysfunction. Limited data exists on the reproductive outcomes of women in the years following a fistula repair. The objective of this study is to describe the fertility outcomes and family planning practices in a population of Malawian women 1-4 years after fistula repair. Methods Women who had enrolled into a clinical database of OF patients and undergone OF repair between January 1, 2012 and July 31, 2014 were recruited and enrolled to complete a home-based survey of their demographic and reproductive health data 1-4 years after their repair. Pregnancy, amenorrhea, and sexual function were described using frequency analysis, and we compared antimüllerian hormone (AMH) concentrations between women with menses or pregnancy with women with amenorrhea or no pregnancy using Wilcoxon rank sum tests. Results Of 297 women with a prior OF repair, 148 had reproductive potential and were included in this analysis. Overall 30 women of these women (21%) became pregnant since their fistula repair, with most pregnancies ending with cesarean delivery. Of the 32 women who were amenorrheic at the time of repair, 25 (78.1%) had resumption of menses. Only 11 (8.6%) of sexually active women reported dyspareunia, and among women who were not trying to conceive, 53.1% were currently using a method of family planning. No significant differences were found in AMH concentrations between those who were pregnant or had menses versus those without pregnancy or menses, respectively. Conclusions In this long-term follow-up study of women after OF repair, many women were able to achieve a pregnancy with a live birth, have normal menses, be sexually active, and access contraception. These achievements will further assist a population of women whose reintegration and restoration of dignity is closely tied to their ability to achieve their reproductive goals. Trial registration ClinicalTrials.gov Identifier: NCT02685878 .